2015
DOI: 10.1128/aac.04917-14
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Protects Paracoccidioides brasiliensis from the Effects of Antimicrobial Photodynamic Inhibition and Antifungal Drugs

Abstract: c Paracoccidioidomycosis (PCM) is a public health concern in Latin America and South America that when not correctly treated can lead to patient death. In this study, the influence of melanin produced by Paracoccidioides spp. on the effects of treatment with antimicrobial photodynamic inhibition (aPI) and antifungal drugs was evaluated. aPI was performed using toluidine blue (TBO) as a photosensitizer and a 630-nm light-emitting diode (LED) light. The antifungals tested were itraconazole and amphotericin B. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…Arthroconidia of N. dimidiatum isolates were more tolerant to APDT with all the four phenothiazinium PS than the hyaline isolates (see Table 5). The protective effect of melanins and melanin-like pigments against conventional antifungal drugs [61][62][63] and also to APDT [64][65][66][67] was observed previously both in conidia and in vegetative yeast cells. Pigmented conidia of Penicillium and Metarhizium are much more resistant to APDT with different PS than the colorless mutants [65][66].…”
Section: Discussionsupporting
confidence: 64%
“…Arthroconidia of N. dimidiatum isolates were more tolerant to APDT with all the four phenothiazinium PS than the hyaline isolates (see Table 5). The protective effect of melanins and melanin-like pigments against conventional antifungal drugs [61][62][63] and also to APDT [64][65][66][67] was observed previously both in conidia and in vegetative yeast cells. Pigmented conidia of Penicillium and Metarhizium are much more resistant to APDT with different PS than the colorless mutants [65][66].…”
Section: Discussionsupporting
confidence: 64%
“…One of the described functions for melanins produced by pathogenic fungi is the protection against antifungal drugs. This was observed for eumelanin producing fungi like Cryptococccus neoformans [ 22 , 31 ], Paracoccidioides brasiliensis [ 32 , 33 ], Histoplasma capsulatum [ 22 ], and Penicillium marneffei [ 34 ]. However, DHN-melanin producing strains of Fonsecaea monophora strains expressing melanin without precursors were not found to protect against antifungals [ 35 ] whereas DHN-melanin from Madurella mycetomatis and Aspergillus fumigatus were able to reduce the effects of ketoconazole and itraconazole [ 36 ].…”
Section: Discussionmentioning
confidence: 92%
“…complex on the effects of treatment with antimicrobial photodynamic inhibition (aPI) and antifungal drugs was evaluated [132]. These authors demonstrated that aPI can reduce the viability of Paracoccidioides spp.…”
Section: Defenses To Host Environment Stressorsmentioning
confidence: 99%